2023
DOI: 10.3390/en16124750
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Water Extraction (HWE) Method as Applied to Lignocellulosic Materials from Hemp Stalk

Abstract: The article describes the process of hot water extraction treatment of a specific material—in this case, shavings of hemp shives of different thicknesses, sorted by their thickness into three different fractions of 0–4 mm, 4–8 mm, and 8–12 mm. In addition, each sample from a given fraction was separately subjected to one, two, and three extraction processes. After the material was treated with extraction, cellulose determination was performed using the Kürschner–Hoffer method in order to find out the effect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The ability of hemp to produce organic [18] and sustainable biofuels [14] has sparked growing interest in the plant in recent years because of its potential applications. The sustainable management of natural resources can be facilitated through the use of hemp as a lignocellulosic raw material [19].…”
Section: Possibilities Of Hemp Based Biofuelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of hemp to produce organic [18] and sustainable biofuels [14] has sparked growing interest in the plant in recent years because of its potential applications. The sustainable management of natural resources can be facilitated through the use of hemp as a lignocellulosic raw material [19].…”
Section: Possibilities Of Hemp Based Biofuelsmentioning
confidence: 99%
“…The versatility of their use can also mean that they are suitable for different applications, like cellulose and lignin. The scientific literature suggests [18,26] that hemp (Cannabis sativa L.) biomass may be a promising biofuel source due to its rapid growth and lower pesticide requirements. There are several ways to use hemp for biofuels, including the production of bioethanol, biogas, and solid biofuels.…”
Section: Possibilities Of Hemp Based Biofuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that hemp is a biofuel feedstock that is highly calorific and has a low ash content, which is why it is a popular feedstock for biofuel production as well [15]. Hemp fiber is capable of containing a value of over 18 J/kg of energy, while wood only has a value of 17 J/kg of energy [16][17][18]. It has been reported that during the combustion process of hemp biomass, the emission values are approximately 0.8 kg CO 2 /kg and do not exceed 0.1 kg CO/kg by weight of raw material as far as CO is concerned [19].…”
Section: Tested Materialsmentioning
confidence: 99%
“…As a result of their action, the physical and strength properties deteriorate, so that the durability of an object composed of unprotected wood is also reduced. Unfortunately, the proper protection of wood against the factors that cause its degradation requires knowledge from many different scientific fields, such as physics, chemistry, construction, and biology [17], so that the person responsible for the protection of wood has sufficient knowledge to use the appropriate measures for the type of factor to which the wood is exposed. Correctly assessing the impact of the site conditions on wood is particularly important for wood used in the construction and boatbuilding industries, where weakening in its strength can lead to catastrophic accidents, such as the collapse of a wooden floor or deck.…”
mentioning
confidence: 99%